KEBIJAKAN PENGHAPUSAN BADAN STANDAR NASIONAL PENDIDIKAN (BSNP) - Anisa Nur Rahmawati; Farid Setiawan; Danu Aprianto; Hesty Andriani Tampubolon; Whulan Kinanti Nur Aini; Hizbullah Muhammad Huda (AL-MUADDIB: Jurnal Kajian Ilmu Kependidikan, 2022)
Education is one of the institutions or institutions that educate the nation and state. As a subject, students are expected to be able to become the nation's next generation who are capable and beneficial to society. Educators and educational institutions play an important role in a school's progress. Likewise with curriculum renewal. The curriculum that is always updated triggers several things that affect practitioners and even education experts propose new things, one of which is related to the abolition of the BSNP (National Education Standards Agency) policy to become the Standards, Curriculum and Assessment Agency. Associated with this renewal triggers several aspects of the latest aspects in the world of education. The purpose of this article is to find out the nature of the National Education Standards Agency (BNSP), the foundations in the National Education Standards Agency (BNSP), as well as the assessment standards in BNSP and how reforms are related to the Standards, Curriculum and Assessment Agency. The method used is library research method. The collection technique is manual and digital. After all the references have been collected, the writer tries to describe and analyze the research results according to the themes discussed.Keywords: Elimination, Policy, BSNP